Efficiency Of Drinking Water Services In The Karrada Municipal Unit (Journal of the College of Basic Education, 2024)
This research aims to evaluate the efficiency of drinking water services in the Karrada municipal unit by analyzing data related to weak water pressure, frequent water outages in the Karrada areas, and water pollution in the Karrada areas. The drinking water service is considered the most important service due to its direct connection to the lives of residents and public health, and The researcher adopted the descriptive analytical approach to reveal the extent of the efficiency of drinking water services in the Karrada municipal unit, with the help of a field study to provide the necessary data for the research. The results showed a high percentage of residential units suffering from weak water pressure: the results indicate that 61% of the residential units in the sample suffer from From weak water pressure, 40.75% of the residential units in the sample suffering from frequent water outages, and 50.5% of the residential units in the sample suffering from water pollution. The study came up with a set of recommendations, including: increasing the capacity of water pumping stations, repairing main water lines, increasing the amount of available water, improving the efficiency of the water network, and educating citizens about rationalizing water consumption.